Assessment of the Level of Constitutionalism in Transition Economies - HARUTYUNYAN, Gagik; SARGSYAN, Hayk; GEVORGYAN, Ruben (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
This work proposes a methodology for a comparative analysis of the level of constitutionalism and a methodology based on it for constitutional diagnosis and monitoring. This technique is particularly useful for studying the level of constitutionalism in transition countries. It has succeeded in classifying countries by level of constitutionalism and determining their cluster-forming factors.